2020
DOI: 10.3390/ijerph17061922
|View full text |Cite
|
Sign up to set email alerts
|

Malaysian Child Restraint Issues: A Brief Narrative Review

Abstract: The child restraint legislation in Malaysia becomes mandatory from 1 January 2020. Prior to commencement of the rule, a survey showed that only 36% of Malaysian parents were aware of the importance of a child restraint system (CRS) and only 27% usage was reported during travel. The Malaysian Institute of Road Safety report showed that children transported in private vehicles were the leading groups of casualties among children aged 1 to 4 years old (43.8%) and 5 to 9 years old (30.2%), respectively. We perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…For the use of a CRS, this would refer to giving weight to the road crashes that affect children's safety (for example, getting in a road accident being the worst) or to the view that children's health is the most important, and giving importance to the safety of your child/children when driving [7,18]. (3). Perceived susceptibility refers to individuals' direct beliefs regarding their own behavior.…”
Section: Health Belief Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…For the use of a CRS, this would refer to giving weight to the road crashes that affect children's safety (for example, getting in a road accident being the worst) or to the view that children's health is the most important, and giving importance to the safety of your child/children when driving [7,18]. (3). Perceived susceptibility refers to individuals' direct beliefs regarding their own behavior.…”
Section: Health Belief Modelmentioning
confidence: 99%
“…A child restraint system (CRS) includes a child safety seat and booster seat designed specifically to protect children from severe or fatal injury in vehicle crashes [3]. A study in Greece found that children aged 0-11 years sitting in front seats and not using child safety seats had a greater risk (up to 5 times) of injury than those in the rear seat using safety seats [4].…”
Section: Introductionmentioning
confidence: 99%
“…The best way to increase the use of CRS is to change parents' perceptions and attitudes towards the use of CRS (8). Due to immaturities in children's physical and mental development and inadequacies in their self-judgment and ability to self-protect, parents are the main guardians of children's safety (9,10). However, studies suggest that the rate of CRS use is extremely low due to a lack of parents' knowledge about CRS use, and poor safety-related beliefs and awareness of child passengers (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Child restraint system or can be called as booster seat is a seat designed especially for children or small adult. The advantages of using CRS are it can help to protect or avoid the user from any injury or death during motor crashes [2][3][4][5][6]. During past 40 years, various child restraint system has been developed to enhance the protection for children or small adults.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 30 percent of all road traffic fatalities occur while people are in their vehicles. First and second on the list of fatalities among children aged 1 to 4 and 5 to 9 years old in Malaysia are those carried in private automobiles (43.8 percent and 30.2 percent, respectively) [2]. In China, according to data from China's Ministry of Public Security's Traffic Management Bureau, there were 27,735 traffic-related deaths of children under the age of 15 between 2005 and 2010 [3].…”
Section: Introductionmentioning
confidence: 99%